A Facile Surface Passivation Method to Stabilized Lithium Metal Anodes Facilitate the Practical Application of Quasi‐Solid‐State Batteries. Issue 11 (11th February 2022) - Huang, Kangsheng; Yu, Jiahui; Wu, Langyuan; Li, Zhiwei; Xu, Hai; Dou, Hui; Zhang, Xiaogang
Abstract: Lithium metal anode matching solid electrolyte is an effective way to achieve high safety and high specific energy batteries, while the active interface of lithium metal has become a bottleneck problem that limits its application. Here, the challenges by forming an artificial solid electrolyte interphase (F‐, B‐containing) on lithium metal surface are surmounted. It demonstrates an extended cycling life over 2000 h of continuous plating/stripping at a high current density of 1.5 mA cm −2 . Nuclear magnetic resonance spectra prove the effectiveness of anion receptors for decoupling Li + ‐F − . The distribution and morphological features of the LiF/B artificial hybrid interphase can be observed from energy‐dispersive spectroscopy and scanning electron microscopy. Specifically, the treated metal lithium anode is also stable in the quasi‐solid‐state pouch cell (polyvinylidene fluoride‐hexafluoro propylene‐LLZTO) system, which can make the rotor of the small aircraft rotate quickly and stably for 9.2 min. Abstract : Lithium metal anode matching solid electrolyte is an effective way to achieve high safety and high specific energy batteries, while the active interface of lithium metal has become a bottleneck problem that limits its application. A reasonable artificial solid electrolyte interphase film design can effectively suppress the problem of lithium dendrites and improve the electrochemical performance and safety of lithium metal batteries.